2013
DOI: 10.3389/fmicb.2013.00188
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of blaESBL–harboring conjugative plasmids identified in multi-drug resistant Escherichia coli isolated from food-producing animals and healthy humans

Abstract: Background: Extended-spectrum β-lactamase (ESBL)-encoding genes are frequently mapped to plasmids, yet few of these structures have been characterized at the molecular level, to date.Methods: Eighty-seven ESBL-producing Escherichia coli were isolated from fecal samples of food-producing animals and healthy humans in Switzerland from 2009 to 2011. Plasmid DNA of all isolates was purified. Broth mating assays were carried out individually for 32 isolates to determine if the ESBL marker could be transferred by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 46 publications
5
60
1
1
Order By: Relevance
“…This result is in agreement with data from previous studies, which demonstrated that bla CTX-M-1 is one of the most prevalent ESBL genes detected in Enterobacteriaceae of broiler origin (45)(46)(47)(48). Also in line with studies performed on broiler farms, the most common replicons encountered in this study were IncI1 and IncFIB (49,50). Moreover, we have found five isolates with the same ESBL gene harbored in two different plasmids.…”
Section: Discussionsupporting
confidence: 82%
“…This result is in agreement with data from previous studies, which demonstrated that bla CTX-M-1 is one of the most prevalent ESBL genes detected in Enterobacteriaceae of broiler origin (45)(46)(47)(48). Also in line with studies performed on broiler farms, the most common replicons encountered in this study were IncI1 and IncFIB (49,50). Moreover, we have found five isolates with the same ESBL gene harbored in two different plasmids.…”
Section: Discussionsupporting
confidence: 82%
“…The virulence and resistant genes found in APEC have been detected on IncFIB plasmids, such as pAPEC-1 (Mellata et al, 2012). All plasmid replicons reported in the current study have been previously detected in E. coli isolates sourced from the environment, other animals and humans (Bortolaia et al, 2010;Garcia-Fernandez et al, 2008;Kluytmans et al, 2013;Lynne et al, 2012;Seni et al, 2016;Wang et al, 2013a;Woodford et al, 2007).…”
Section: Investigating the Prevalence Of Carriage Of Avian Pathogenicmentioning
confidence: 78%
“…The IncI1, IncFIB, IncY and IncN plasmids have been identified in poultry previously and were associated with MDR and ESBLs producing E. coli (Bortolaia et al, 2010;Garcia-Fernandez et al, 2008;Kluytmans et al, 2013;Lynne et al, 2012;Seni et al, 2016;Wang et al, 2013a). One of the ESC resistant isolates contained IncY and IncI1 plasmid types, while the other contained IncFIA, IncFIB and IncFrep plasmids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This establishes a transferability of 28.57% which is almost in concordance with results (30%-80%) of other similar studies. 7,[21][22][23] These two strains and another one (from HiMedia Kit) were further experimented to document the effects of Acriflavine.…”
Section: Discussionmentioning
confidence: 99%